FRI0321 Association between Disease Severity and Patient-Reported Outcomes in Patients with Discoid Lupus Erythematosus in Real-World Clinical Practice. (15th July 2016) - Hoskin, B.; Lobosco, S.; Bell, D.; Kao, A.; Hall, S.; Chen, S.-Y.
Abstract : Background: Cutaneous diseases are often associated with high humanistic burden. Current understanding of the patient perspective among those with discoid lupus erythematous (DLE), a chronic disease disproportionately affecting minorities, is particularly lacking. We undertook this analysis to gain insight into the patient perspective on the impact of DLE, and how impact might vary across severity levels. Objectives: To assess the patient's self-reported burden associated with disease severity and perceived unmet need amongst moderate-to-severe vs. mild DLE patients from a real-world setting. Methods: Data were drawn from a multinational survey of 101 dermatologists across the US and EU (France, Germany, Italy, Spain & UK) conducted in 2013. Dermatologists completed patient record forms (PRFs) for their next five prospectively consulting patients with cutaneous lupus erythematosus and patients provided data via self-completion forms (PSCs). Patient-reported outcomes (PROs) collected in the PSC included the EuroQol 5D (EQ5D), visual analog scores, work and activity impairment indices, and the functional assessment of chronic illness therapy scale (FACIT-Fatigue). For the current visit, patients were categorized by dermatologists into moderate/severe vs. mild groups. PRO measures by severity status were compared in bivariate analyses, using Mann-Whitney-U tests and Fisher's exact tests. Results: A total of 180 DLE patients in the EU and US provided PSC data and were included in the analyses (mean age 39.5, disease duration 3.9 years, majority female [69%]) At the current visit, 25% of DLE patients were categorized as having moderate-to-severe disease. These patients self-reported a significantly and clinically lower EQ5D score compared to mild patients (0.86 vs. 0.94; p=0.0004), whilst also reporting a lower visual analog score (66.0 vs. 76.8; p=0.0005) indicating worse health-related quality of life. The reported impact of fatigue was also significantly greater amongst moderate-to-severe patients (FACIT-Fatigue score 36.0 vs. 43.4 among mild; p=0.0004). Moreover, moderate-to-severe DLE patients reported a greater degree of overall work impairment (30.0% vs. 18.0%; p=0.0612) and activity impairment (30.0% vs. 17.9%; p=0.0178). Finally, self-reported satisfaction with disease control was also significantly lower amongst these moderate-to-severe DLE patients (55% satisfied vs. 84%; p<0.0001). Conclusions: As reported by patients from a multinational sample in clinical care and compared to having a mild disease, having moderate-to-severe DLE was associated with a negative impact on quality of life, the ability to work and the ability to participate in activities, and satisfaction with disease control. Our research using PROs in a real-world setting, rather than in a clinical trial, adds to our limited understanding of the humanistic impact of DLE. Acknowledgement: These analyses were supported by Biogen. Disclosure of Interest: B. Hoskin: None declared, S. Lobosco Employee of: Adelphi Real World, D. Bell Employee of: Adelphi Real World, A. Kao Employee of: Employee at Biogen at the time of the research, S. Hall Shareholder of: Biogen, Employee of: Biogen, S.-Y. Chen Shareholder of: Biogen, Employee of: Biogen